Avaliação da utilização de argilas em poliestireno de alto impacto reciclado de equipamentos eletroeletrônicos (REEE) - Consul, Thiago Bueno (2018)
Due an annually increase of polymer production, lots of residues are being generated and recycled by low technology investments and it is used to produce simple material, as bags and containers. However, engineering polymers that have specific properties, and toxic components that could cause harm to humans, require proper sorting and recycling. Waste electrical and electronic equipment (WEEE) residues have these characteristics polymers and is not suitable to discard high value residues because of its economic and environmental inviability. In this context, the recycled high impact polystyrene from this study is important and the second most used polymer in EEE due to its mechanical properties. Two different methods were used, compression molding with heating was used in a hydraulic press with recycled HIPS and different types of bentonite clays (untreated from Tecmas and CloisiteNa and also organophilic clays as Claytone 40 and Cloisite 15A). Also, these composites were also obtained by extrusion with each clay to improve its dispersion and molded by compression with heating in the same hydraulic press. The composites were mechanically evaluated in tensile, flexural and impact strength, as also for thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC).The results of the mechanical tests of the recycled HIPS presented values close to the virgin HIPS of the literature. The tensile strength results from composites with Tecmas and CloisiteNa clays (14.25 ± 2.02 and 11.46 ± 4.06 MPa) were close to the recycled HIPS (12.74 ± 0.51 MPa to 13.28 ± 0.60 MPa). Recycled HIPS tensile modulus and its composites were similar and with values around 1400 MPa. However, the use of organophilic clays reduced the mechanical tensile and flexural properties of the composites. Impact strength from HIPS/Tecmas clay composites (90.8 ± 7.8 J/m) were close to recycled HIPS (88.5 ± 7.0 e 98.9 ± 13.4 J/m), other composites were under 80 J/m. Similar results were obtained with extruded composites of HIPS/Clay in mechanical tests. Thermogravimetric analysis demonstrated variation in graphic curves with higher temperatures related to the elastomer degradation and better clay interaction due its organophilic properties. While in DSC results were not possible to observe any variation in temperatures related to polybutadien and polystyrene. Despite the decrease in some mechanical properties from the composites, using clay is an option for flame retardancy and to smooth polymer reclying and molding of new materials.